The effectiveness of social dynamics-based group counseling on changes in students’ smoking behavior: A systematic review - Ridho, Akta; Defriyanto, Defriyanto (Universitas Islam Negeri Raden Intan Lampung, 2026)
Adolescent smoking behavior is a significant public health and psychosocial problem influenced by self-efficacy, peer influence, social norms, and school environment. Conventional educational approaches tend to increase knowledge but are less effective in producing sustained behavioral change. This study aims to synthesize evidence on the effectiveness of social dynamics-based group counseling in changing students’ smoking behavior. This study employed a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines using Scopus-indexed articles published between 2019 and 2026. A total of 36 studies were included, consisting of 17 direct intervention studies and 19 supporting studies on psychosocial mechanisms. Data were analyzed using narrative and thematic synthesis. Findings indicate five key domains influencing effectiveness: self-efficacy, anti-smoking social norms, peer social support, peer-led interventions, and implementation fidelity. Group-based and peer-led interventions show stronger effects on smoking cessation intentions, social norm formation, and resistance to peer pressure compared to one-way education and media campaigns. However, long-term behavioral change remains inconsistent and is influenced by school context, program quality, and follow-up duration. This study highlights that social dynamics-based group counseling has potential as a school preventive strategy through strengthening self-efficacy, social norms, and peer support. Further longitudinal and experimental studies are required to confirm long-term effectiveness.